Integrating Hikmah Values into Sustainable Housing Development: Evidence from Muslim Communities in Bone Regency, Indonesia - Andi Lisa Aryani Hamjan; Sitti Nikmah Marzuki; Ida Farida (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines how hikmah (Islamic wisdom) is implemented in housing property development among Muslim communities in Bone Regency, how sustainable housing development is realized in that context, and how hikmah strengthens community perceptions of sustainable housing. Methodology: A qualitative descriptive field research design was used. Ten purposively selected informants (residents, a developer, a housing-association representative, government officials, and an academic) were studied through semi-structured interviews, non-participatory observation, and documentation, analyzed with NVivo 12 using coding, data display, conclusion drawing, and source/technique triangulation. Main Findings: Hikmah operates at conceptual (economic, environmental, social, spiritual) and operational (institutional governance, area planning) levels. Sustainability experienced by residents is predominantly social and spiritual rather than ecological or financial, with places of worship acting as a centripetal force. Community perception strengthens through consistent realization of developers' promises rather than normative rhetoric, though a regulatory vacuum and conceptual-standardization gap persist. Novelty/Originality of this study: The study proposes a Hikmah-Based Property Development Model that integrates four dimensions of hikmah as a contemporary maqāṣid al-shariah framework applied to housing, extending the Brundtland sustainability definition and SDG 11 with a spiritual-community pillar not previously articulated in sustainable-housing literature.